2023
DOI: 10.2147/jhc.s404895
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Analysis of Single Large Hepatocellular Carcinoma Following Radical Resection: A Single-Center Study

Abstract: Objective To investigate the survival and independent prognostic factors for single large hepatocellular carcinoma (SLHCC) after surgical resection. Methods Patients with SLHCC who underwent radical resection from January 2013 to December 2017 were retrospectively analyzed. The Kaplan-Meier method was used to analyze the overall survival (OS) rate and recurrence-free survival (RFS) rates. Cox forward stepwise regression was performed to analyze the independent prognosti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“… 22 Additionally, cirrhosis is an independent prognostic factor in patients with solitary HCC. 28 Our study found that none of the patients with solitary HCC who underwent AR developed postoperative liver failure. Based on the results of subgroup analysis, we observed that wide RM improved the prognosis of patients with ALBI grade I, the absence of cirrhosis, or hepatitis B infection.…”
Section: Discussionmentioning
confidence: 51%
“… 22 Additionally, cirrhosis is an independent prognostic factor in patients with solitary HCC. 28 Our study found that none of the patients with solitary HCC who underwent AR developed postoperative liver failure. Based on the results of subgroup analysis, we observed that wide RM improved the prognosis of patients with ALBI grade I, the absence of cirrhosis, or hepatitis B infection.…”
Section: Discussionmentioning
confidence: 51%